Effect of Biofield Treatment on Growth and Physiology of Hydroponically-Grown Lettuce and Bok Choy Plants - Chia-Tung Lee; How-Chiun Wu (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The aim of this study was to investigate the effects of biofield treatments on the growth and physiology of lettuce and bok choy plants. Energy art pieces and water treated by energy art were used as biofield treatments. Overall, both the lettuce and bok choy plants exposed to a combination of energy art and energy art-treated water were significantly larger in terms of leaf and root growth than those in the other treatments. Clear improvements in the vegetative growth of these plants were found, as seen in the significantly higher number of leaves, leaf dry mass, and leaf area. Furthermore, the highest chlorophyll and carotenoid contents were detected in lettuces and bok choy cultivated in the energy art and energy art-treated water treatments, respectively, which were significantly higher than those grown in the control. Moreover, the photosynthetic efficiency of the lettuce and bok choy plants exposed to the energy treatments were improved significantly. The results of this study demonstrated significant effects of biofield in the form of energy art and energy art-treated water on hydroponically-grown lettuce and bok choy plants. Biofield treatments such as energy art can be used as an alternative approach to improve plant growth and yield.